STUDIES ON REFINED LIQUISOLID SYSTEM FOR SIMULTANEOUS IMPROVEMENT OF CONTENT UNIFORMITY AND DISSOLUTION PROFILE OF GLIMEPIRIDE - Dhall, Manish; Phaugat, Parmita; Nishal, Suchitra (International Journal of Applied Pharmaceutics, 2019)
Objective: To improve and compare dissolution contour of poorly soluble BCS Class II drug Glimepiride (GLD) by altering it to conventional solid dispersion (CSD), surface solid dispersion (SSD) and refined liquisolid system (RLS). Methods: The three formulations of GLD namely CSD, SSD and RLS were fabricated using the conventional methods by employing the suitable polymer and solvent system. These formulations were optimized on the basis of powder flow properties, FTIR, DSC and XRD analysis. All the optimized formulations were compared to the marketed formulation for content uniformity and dissolution rate. Results: The characteristic analysis of all the optimized formulations was obtained in the standard range. The average content uniformity (% age) of Marketed formulation, CSD, SSD and RLS found to be 88.28±0.721, 92.91±0.789, 95.98±0.478, 99.32±0.744 respectively. The in vitro dissolution rate (%age at 30 min time interval) fall in the range 59.78±0.036, 75.78±0.013, 93.11±0.019, 93.99±0.062 and 98.55±0.043 for pure drug, Marketed formulation, CSD, SSD and RLS respectively. All the analytical studies exhibited improved homogeneity/distribution of the drug in RLS. Conclusion: The RLS formulation presented sheer expansion in the content uniformity and dissolution contour of GLD at a minimal cost.